Perception of Healthcare Professionals toward Clinical Pharmacy Services - AlDehemi, Ahmed Mohamed; Khashaba, Dr. Ahmed Sayed (International Journal of Innovative Research in Medical Science, 2017)
Introduction Based on American College of clinical pharmacy (ACCP), Clinical pharmacy is defined as that area of pharmacy concerned with the science and practice of rational medication use (The Definition of Clinical Pharmacy, 2008). The European Society of Clinical Pharmacy (ESCP) defines clinical pharmacist as "A health specialty, which describes the activities and services of the clinical pharmacist to develop and promote the rational and appropriate use of medicinal products and devices". The clinical pharmacist has a variety of responsibilities which include the performance of patient assessment, ordering drug therapy related laboratory tests, administering drugs, selecting, initiating, monitoring, continuing and adjusting drug regimens (Clinical Pharmacy et al., 2003).